Model dvojezičnega pouka v Prekmurju in slovar kot didaktični pripomoček - Rudaš, Jutka (Slovenščina 2.0, 2017)
The model of bilingual education is one of the two-way models of preserving two languages and cultures. This paper describes the successful implementation of a bilingual education process, with a short developmental span and an emphasis on the key deficiencies of the model. By getting to know two cultures and two social relationships and by understanding them, pupils develop a positive attitude to cultural diversity as well as intercultural relationships. Within the framework of school subjects, we teach professional terminology in both languages and thus educate speakers in a way that they experience linguistic and cultural diversity in the ethnically mixed area of Prekmurje. The model of the two-way preservation of the mother tongue makes sense only if the community and the society benefit from bilingualism, and if important and above-average intercultural and social competences that contribute to peaceful coexistence of different cultures are allowed access. Practice shows that so far these goals have not been fully implemented, that there is no ideal relationship between the languages of instruction and that the desired results are not implemented. We have found that there are two shortcomings in this respect: the incomplete didactic aspect and the inadequate competence of teachers in bilingual educational institutions owing to the lack of possibility of acquiring the appropriate competences, particularly in the Hungarian language. Among the most important means for the efficiency of the language structure acquisition and language use are bilingual textbooks and other teaching aids. Based on these findings, this paper presents cognitive and other skills that enable the integration of a bilingual dictionary into the teaching process. As this is a demanding and important skill, it is crucial that teachers and pupils are trained in this activity. The dictionary as a didactic tool is not merely a means of information but also a basis for the development of skills at various language levels. This is undoubtedly true also for modern, useful dictionaries, designed with innovative lexical approaches and with all the advantages of electronic media in combination with other didactic tools and technologies. We also present two important projects that have improved the situation in bilingual education by developing dictionaries and e-materials, and providing teachers with skills for using them in class. We conclude that teachers and students in bilingual education in Prekmurje are now better equipped for their work. Also, a recently published call for research projects into bilingual education in Slovenia indicates that more improvements to the bilingual education model in Prekmurje can be expected.
Keywords: Slovene; Slovenian language; slovenščina; Hungarian; Hungarian language; madžarščina; dvojezična vzgoja in izobraževanje; bilingual education; didactic method; didactics; didaktika; dvojezični slovarji; bilingual dictionaries; materni jezik; native language; second language; drugi jezik; jezikovne kompetence; language competences; Prekmurje; Prekmurje region